2014
DOI: 10.5935/medicalexpress.2014.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology of ibuprofen in preterm infants: A meta-analysis of published data

Abstract: OBJECTIVES: Ibuprofen is a non-selective anti-inflammatory cyclooxygenase inhibitor drug of the propionic acid class of non-steroidal agents, available without prescription in the USA. In preterm infants, ibuprofen is used to close the Patent Ductus Arteriosus and it was found to be more effective than indomethacin. This metaanalysis determined whether differences exist in the closure rate of Patent Ductus Arteriosus following the oral vs. intravenous ibuprofen administration to preterm infants; it examines me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Although this finding may appear counterintuitive, available pharmacokinetic data support this observation . Pacifici postulated that a slower absorption rate along with a longer half-life prolong the time of contact with the PDA, leading to higher responsiveness of oral ibuprofen compared with the intravenous formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although this finding may appear counterintuitive, available pharmacokinetic data support this observation . Pacifici postulated that a slower absorption rate along with a longer half-life prolong the time of contact with the PDA, leading to higher responsiveness of oral ibuprofen compared with the intravenous formulation.…”
Section: Discussionmentioning
confidence: 99%
“…This was also seen in a large network meta-analysis ( 74 ). Pacifici suggested that the slower absorption and prolonged half-life with oral administration offered more time for the drug to interact with the PDA and thus made it more effective ( 89 ). However, a study of ELBW infants found that those infants who received oral ibuprofen for PDA closure had a higher rate of PDA reopening compared to those who received IV ibuprofen ( 90 ).…”
Section: Medical Closure Of a Hemodynamically Significant Pdamentioning
confidence: 99%